The Values of Social Education in the Qur’an and its Relevance to The Social Character Building For Children - Athoillah Islamy; Saihu (Paedagogia: Jurnal Pendidikan, 2019)
This study aims to find the values ​​of social educational contained in the Qur'an. This research is a qualitative research in the form of library research. The focus of the verse is the object and source of primary data of this study, namely various commentaries that explain Surah at-Taubah verses 71-72. While secondary data sources of research is various literatut that are relevant to the subject matter of discussion. To answer the discussion of the research, the writer uses the method of interpretation maudhu'i (thematic). This study concludes that the values ​​of humanistic social education contained in the letter at-Taubah verses 71-72 include attitudes of helping to help, an invitation to the good and preventing munkar, social solidarity, brotherhood. These values ​​can be a spirit of social education in forming empathy, mutual care, protection, tolerance and high social solidarity. The four values ​​of social education can be actualized in the context of the planting of social education in children through various things, among others, the cultivation of a noble mentality in children can be realized in the planting of brotherly values ​​and help children. Furthermore, the cultivation of a spirit of attention to the rights of others and a commitment to social ethics can be realized through the inculcation of the value of social solidarity. Then, inculcation of critical and social supervision can be realized by instilling the value of amar makruf nahi munkar.